Dynamic Linguistic and Artistic Patterns in Jonson’s THE ALCHEMIST - Raza, Dr. Amra Raza (Journal of Research in Humanities, 2023)
This paper attempts to demonstrate how and why Ben Jonson’s play The Alchemist is a valuable literary and historical document in that it charts important shifts and changes in the English language at the lexical, grammatical and semantic levels. A detailed linguistic study of the play reveals how specific words were borrowed and accommodated from various languages into English. The Alchemist also reveals significant aspects of social change in the idioms drawn from rural life, legal and even culinary jargon at that time. The investigation also touches upon a brief semantic analysis and examines the use of some speech acts in the play which enriches its dramatic significance.